Composition for impregnating substrates, in particular watch straps
Patent Information
- Application Number
- JP2020091888
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-31
- Filing Date
- 2020-05-27
- Publication Date
- 2025-02-13
- Estimated Expiration
- 2040-05-27
Smart Images

Figure 0007629275000013 
Figure 0007629275000014 
Figure 0007629275000015
Abstract
Description
[Technical field]
[0001] explanation There is a need to improve the lifespan of watch straps without affecting the natural look and feel of the leather. Compositions have been synthesized that allow for improved water repellency and microbial resistance. Finished leather watch straps can be treated with the compositions to improve customer satisfaction.
[0002] Advantageously, the leather watch straps can be processed fully assembled and can include straps from a variety of suppliers, allowing the customer to distinguish their genuine strap from other straps available on the market.
[0003] FIELD OF THEINVENTION The present invention relates to compositions and treatments for leather, vegetable hides, or textiles used, inter alia, as watch straps.
[0004] The composition comprises an active organic compound (sometimes referred to in the present description as "active molecule") comprising a phosphonic acid group and one or more hydrophobic or superhydrophobic functional groups (in particular alkyl groups, preferably fluorinated alkyl groups), and optionally an antifouling functional group (preferably a polyalkylene glycol group) and / or a bioactive functional group (in particular an ammonium, imidazolium, or triazolium group). [Background technology]
[0005] overview Technical problems to be solved Leather watch straps and leather jewelry are natural products that evolve over time. Due to current wearing conditions, especially contact with water and the wearer's skin, they will deteriorate rapidly, both aesthetically and olfactorily. The rapid deterioration of leather watch straps or leather jewelry is due, among other factors, to the exposure of the watch strap to moisture, water, and various organic substances (sweat, soap, dirt, etc.) resulting from the activities performed during wear. Furthermore, a leather watch strap can be a composite combination of different types of leather and / or other materials. It can include liners, finishing layers, stuffing, etc. The stuffing can be in leather or another material. However, users want to keep the natural look and feel of the leather as long as possible.
[0006] A brief explanation of the solution The solution to this problem proposed by the present invention consists in applying a composition to the watch strap or to the elements intended for producing the watch strap such as the outer surface, lining, stitching, and / or to the internal elements such as padding or ripstop elements, etc. This treatment provides hydrophobic and / or biocidal and / or stain resistant properties, which can improve the durability of the watch strap without adversely affecting the look and feel of the watch strap.
[0007] cutting edge technology Porous substrates, such as watch straps, bracelets, or necklaces, are commonly used in articles that come into contact with the skin of a user. These substrates allow water vapor to pass through, making the article comfortable to wear. However, they have varying degrees of water repellency. It is well known that odors in these products are caused by bacterial growth on or within the substrate. However, watch straps, bracelets, or necklaces are not easy to clean.
[0008] The composite structure of porous substrates such as leather poses difficulties in understanding the exact decay pattern of a particular substrate. Decay depends on several factors, including environmental conditions. In the case of leather, its processing is also taken into account. Chemical damage can occur from exposure to environmental factors such as UV light, ozone, acids from sulfur and nitrite pollutants in the air, and sweat. In the case of leather, it is also known that prolonged exposure to low relative humidity (below 40%) can cause drying or irreversible changes in its fiber structure. (Preserver les objets de son patrimoine:precis de conservation preventive;International Institute for Conservation of Historic and Artistic Works.Section francaise;Editions Mardaga,2001;ISBN 2870097662,9782870097663).
[0009] The finishing treatment of substrates such as leather consists in a series of surface manipulations aimed at improving the natural qualities of the substrate and / or covering possible defects present on the surface. Mechanical protection, color uniformity, and tactile properties are the main requirements of the finish. Many acrylic, polyurethane, and other film-forming synthetic polymers are common components of finishing recipes, which are mixed with natural and / or modified natural substances such as oils, waxes, casein, albumin, cellulose esters, and other substances. Numerous patents and papers describe these various methods to improve antimicrobial resistance, water and / or oil repellency, and / or stain resistance.
[0010] Generally, water-resistant or stain-resistant substrates such as leather or textiles are prepared using chemicals that can form functional coatings with low surface free energy on the substrate surface. These coatings can be thin polymeric films including silicones, fluorinated hydrocarbons, or long-chain hydrocarbons. However, the air and water vapor permeability of the treated substrates can be compromised, and the development of new methods to produce such substrates that maintain their natural properties remains a challenge.
[0011] Examples of easy-to-clean coatings based on fluoroalkylsilanes or alkylsilanes, i.e. coatings with oil-, water- and dirt-repellent properties, are described in many documents (e.g. DE 834002, U.S. Pat. No. 3,012,006, GB 935,380, U.S. Pat. No. 3,354,022, DE 1518551, DE 3836815, DE 4218657, DE 19544763, WO 95 / 23830, EP 0799873, EP 0846716, JP 2001 / 115151, EP 1033395, EP 1101787). These coatings protect the leather but can be seen and felt, leading to the perception that the leather has been treated and an artificial appearance.
[0012] Oil and water repellency can be imparted to a surface by hydrolyzable fluorocarbon silanes. Chemical bonds are created between the silane and active hydrogen functional groups on the substrate. This is achieved by first hydrolyzing the hydrolyzable groups on the silane to silanol groups, which then condense with functional groups on the substrate. The more hydrolyzable groups the fluorocarbon silane has that bond with the substrate, the more durable the coating will be (see WO 95 / 23830).
[0013] Leather watch straps containing antibacterial agents are known and are described, for example, in the document DE Utility Model 20315119 (U1). According to this document, a watch strap made of leather comprises an inner band (i.e. a liner) in contact with the wearer's skin, made of leather treated to have antibacterial properties. This strap has the advantage that no bad odors are generated, especially in the case of sweating. However, certain active ingredients incorporated in the strap, such as antibacterial agents, can be irritating or allergenic to the skin, especially in the case of prolonged contact of the strap with the skin, more particularly in hot and humid conditions.
[0014] explanation In this application, unless otherwise stated, the use of the terms "a" or "an" means "at least one," and the use of "or" means "and / or."
[0015] One objective of the treatment of the present invention, referred to in this description as "functionalization", is to reduce or limit the presence of microorganisms that cause unpleasant odors on a watch strap without compromising its appearance and feel. The treated substrate has improved moisture absorption, washability, stain resistance, and / or odor adsorption properties. The functionalization method does not substantially degrade the substrate and maintains its original feel and appearance.
[0016] More specifically, the present invention relates to a functionalizing composition, a method for functionalizing a porous substrate such as natural leather, vegetable leather (Pinatex®, MycoTEX®, Tencel®, eucalyptus, bamboo, rubber tree, etc.), cork or textiles (cotton, hemp, silk, nylon, polyamide, aramid textiles, etc.), and to a functionalized product consisting of said substrate. [Brief description of the drawings]
[0017] [Figure 1] FIG. 13 shows the water absorption of samples related to plasma pressure as shown in Table 2. [Diagram 2]Table 9 shows the water absorption rate (%) of the samples over time after surface treatment obtained in tests 0, 23, 33, and 35. [Diagram 3] Table 10 shows the water absorption (%) versus treatment time obtained in tests 0 and 22 to 25. [Figure 4] Table 11 shows the water absorption (%) versus the concentration of the treatment solution for Tests 0, 23, and 26 to 29. [Diagram 5] The water absorption rate (%) is shown relative to the TEOS-AM_7 ratio. [Figure 6] Schematically, two embodiments of the invention are shown which are described below.
[0018] The present invention provides the following aspects: 1. A composition for impregnating a watch strap or a part thereof, comprising: a) organic solvents or sol-gels; b) at least one active organic compound comprising, preferably consisting of, a phosphonate group -POH and a hydrophobic or superhydrophobic group; c) any one or more functional groups selected from i. antifouling functional groups and ii. bioactive functional groups A composition comprising: 2. The composition according to item 1, wherein the hydrophobic or superhydrophobic group of the active organic compound is a linear or branched alkyl group having 2 to 18 carbon atoms, which may be partially or fully substituted by halogens, preferably by chlorine or fluorine, most preferably by fluorine. 3. The active organic compound is i.CH3(CH2) n PO3H, where n is 2 to 18, or ii.CF3(CF2) n (CH2) m PO3H, where n and m are 2 to 18, and m and n are the same or different. 4. The antifouling functional group of the active organic compound has the formula: -O((CH2) m O) n-, wherein m is 2, 3 or 4, preferably 2, and n is 2 to 18, and has a hydrogen or an alkyl end group having 1 to 6 carbon atoms. 5. The active organic compound is RO(CH2CH2O) n (CH2) m 5. The composition according to item 1 or 4, wherein n and m are 2 to 18, n and m are the same or different, and R is H or CH. 6. The composition according to item 1, wherein the biologically active functional group of the active organic compound is an imidazolium group, a triazolium group, or an alkylammonium group optionally substituted with 1 to 3 alkyl substituents having 1 to 6 carbon atoms, or 0, 1, or 2 alkyl substituents having 1 to 6 carbon atoms, and an alkyl substituent having 10 to 18 carbon atoms. 7. The active organic compound is CH3(CH2) n (N(CH3)2) (+) (CH2) m PO3HCl (-) wherein n and m are 2 to 18, m and n are the same or different, and the compound is 1-methyl-3-(dodecylphosphonic acid)imidazolium bromide, or 1-methyl-3-(dodecylphosphonic acid)imidazolium bis(trifluoromethylsulfonyl)imide. 8. The composition according to any one of items 1 to 7, further comprising bioactive metal nanoparticles, preferably silver nanoparticles. 9. The composition according to any one of items 1 to 8, wherein the solvent is ethanol or isopropanol, preferably ethanol. 10. A method for functionalizing a substrate by impregnation, comprising: i. selecting a substrate; ii. degassing the substrate; iii. treating the substrate with oxygen plasma or air plasma; iv. at least partially impregnating or coating the substrate with the composition according to any one of items 1 to 8, the composition comprising an organic solvent; v. drying the treated substrate; A method comprising: 11. A method for functionalizing a substrate by impregnation, comprising: i. selecting a substrate; ii. preparing a sol-gel solution from hydrolyzable silane precursors under acidic or basic conditions; iii. Aging the sol-gel solution; iv. at least partially impregnating or coating said substrate with said sol-gel solution; v. drying the treated substrate; vi. fixing the sol-gel to the substrate by tempering; A method comprising: 12. The method according to claim 11, wherein the sol-gel comprises an active organic compound according to any one of claims 1 to 9. 13. The method according to any one of items 10 to 12, wherein the substrate is selected from natural leather, natural leather substitutes made from plant fibers, cork, and textiles, and combinations thereof. 14. The method according to any one of items 10 to 13, wherein the substrate is a watch strap or a part thereof. 15. Use of a composition according to any one of items 1 to 9 for reducing the water absorption rate of a substrate, preferably a watch strap or one or more parts thereof. 16. A watch strap obtainable by the method according to any one of items 10 to 14. 17. A watch strap comprising an active organic compound and / or a silica sol-gel network according to any one of items 1 to 9.
[0019] Detailed Description of the Invention Means for solving the problem It is known that microorganisms require water to be active. By generating a hydrophobic or superhydrophobic functionalization of a substrate, it is possible to limit the presence of water in and / or on the surface of said substrate. This affects the activity of microorganisms. As a result, the substrate does not generate unpleasant odors or requires much more time to generate such odors.
[0020] Another way to prevent unpleasant odors is to avoid microbial contamination, which can be removed by simple mechanical actions such as rubbing or wiping the wrist on a substrate. Furthermore, compounds can also exhibit biological activity against microorganisms that cause malodours.
[0021] The limitation of microbial growth on or in leather watch band liners in order to limit the development of abnormal odors can be achieved in two different ways: by antifouling treatment of the surface of the substrate, which limits the adhesion of microorganisms that cause malodours, or by biocide treatment. A combination of antifouling and biocide treatment is also possible. Avoiding the creation of biofilms by microorganisms, dead or not, prevents the development of malodours. Antifouling treatments by limiting the presence of microorganisms avoid or at least limit the appearance of malodours. The deterioration of leather can also be slowed down.
[0022] In all embodiments of the present invention, the inventors have used three approaches: A. Hydrophobic or superhydrophobic treatments may be applied to control the moisture concentration of the substrate and avoid the introduction of water into the substrate. The accumulation and concentration of odor-causing substances can be limited by inactivating microorganisms caused by unfavorable moisture conditions. B. "Anti-fouling" polyalkylene glycol (e.g., polyethylene glycol)-based treatments prevent microorganisms and cells deposited on a surface from adhering to it, so that they can be eliminated by a simple mechanical action such as rubbing the wrist or wiping. C. Treatments to obtain cationic bioactive surfaces have the same "anti-fouling" effect as polyalkylene glycol treatments.
[0023] Approach A can be combined with other approaches according to the invention within one and the same active molecule (active organic compound). In general, the present invention can apply one active molecule or a mixture of two or more different active molecules.
[0024] functional group The active organic compound in the functionalized composition of the present invention has a phosphonic acid group and a hydrophobic or superhydrophobic group. The hydrophobic and / or superhydrophobic group-containing compound used in the composition of the present invention is an alkyl phosphonate or a halogenated alkyl phosphonate, preferably a fluorinated alkyl phosphonate. The alkyl group may be linear or branched and may have from 2 to 18 carbon atoms. The halogenated alkyl phosphonate compound may be fully or partially halogenated. Typical compounds having hydrophobic or superhydrophobic functional groups for use in the present invention are, for example, CH3(CH2) n PO3H, where n is 2 to 18, or CF3(CF2) n (CH2) m PO3H, where n and m are 2 to 18, and m and n are the same or different. Halogenated alkyl phosphonates are preferred, and fluorinated alkyl phosphonates are most preferred.
[0025] The term "phosphonate" is used herein to designate phosphonic acid and its salts. The counterion of the salt can be any suitable cation, such as a metal cation (e.g., sodium, potassium, calcium, magnesium, and any other metal cation that does not impair the properties of the compound), or an organic cation, such as ammonium. Phosphonic acid groups are preferred.
[0026] Preferred hydrophobic or superhydrophobic group-containing active organic compounds for use in the present invention are octylphosphonic acid, dodecylphosphonic acid, n-octadecyl Phosphonic acid, 3,3,4,4,5,5,6,6,6-nonafluorohexadecylphosphonic acid, 12,12,13,13,14,14, 15,15,15-nonafluoropentadecylphosphonic acid, 3,3,4,4,5,5,6,6,7,7,8,8,9,9,10,10,10-heptadecafluorodecylphosphonic acid.
[0027] Optionally, the active organic compound may further comprise at least one of the following functional groups: i. antifouling functional groups; ii. Bioactive functional groups.
[0028] The functional groups according to the invention are selected in order to fulfill at least one of the abovementioned effects. Advantageously, the compounds combine at least two of these effects.
[0029] Compounds that provide an "anti-soiling" effect to the surface of a substrate are, for example, polyalkylene glycols such as polyethylene glycol, propylene glycol, or butylene glycol-containing compounds.
[0030] Additionally, the polyalkylene glycol-containing compounds typically have alkoxy end groups obtained by alkylating a hydroxyl end, such as a methyl, ethyl, propyl, or butyl end group. If the end is not alkylated, the end group is a hydroxy group.
[0031] Compounds which combine a phosphonate group, a hydrophobic or superhydrophobic group with a polyalkylene glycol group are particularly suitable for the compositions according to the invention.
[0032] Compounds in which a hydrophobic or superhydrophobic group is combined with an antifouling group are, for example, RO(CH2CH2O) n (CH2) mPO3H (wherein n and m are 2 to 18, n and m are the same or different, and R is H or CH3). Specific and preferred examples of such compounds which may be used in accordance with the present invention are 6-[2-[2-(2-methoxyethoxy)ethoxy]ethoxy]hexylphosphonic acid, 2-[2-(2-methoxyethoxy)-ethoxy]ethylphosphonic acid, 2-[2-(2-methoxyethoxy)ethoxy]hexylphosphonic acid, 2-[2-(2-hydroxyethoxy)ethoxy]ethylphosphonic acid, 2-[2-(2-hydroxyethoxy)ethoxy]-hexylphosphonic acid, and {2-[2-[2-[2-[2-[2-[2-[2-[2-[2-[2-[2-[2-[2-[2-[2-(2-hydroxyethoxy)-ethoxy]ethoxy]ethoxy]ethoxy]ethoxy]ethoxy]ethoxy]-ethoxy]ethoxy]ethoxy]ethoxy]ethoxy]-ethyl]}phosphonic acid.
[0033] Compounds having a biologically active functional group that imparts cationic properties to the surface of the substrate are, for example, ammonium-, triazolium-, and / or imidazolium-containing compounds. In the case of the ammonium group, the compound contains the ammonium group -NH3, which forms the ammonium by covalent bonding to the rest of the molecule. + or an alkyl substituted ammonium group. It preferably has an alkyl chain of 10-18 carbon atoms on the nitrogen and a short chain alkyl group such as hydrogen or an alkyl group of 1-6 carbon atoms (preferably ethyl). The bioactive functional group is attached to the phosphonate group via the hydrophobic or superhydrophobic group, i.e., it is located at the "other end" of the hydrophobic or superhydrophobic group relative to the phosphonate group.
[0034] The counterion can be any anion, such as halide, sulfate, nitrate, phosphate, trifluoromethylsulfonyl, or other anion of an inorganic or organic acid, with halide and trifluoromethylsulfonyl being preferred, and chloride, bromide, and trifluoromethylsulfonyl being especially preferred.
[0035] The compound that combines superhydrophobic, antifouling, and bioactive groups is CH3(CH2) n (N(CH3)2) (+) (CH2) m PO3HCl (-) (wherein n and m are 2 to 18, and m and n are the same or different).
[0036] Preferred examples of this type of molecule are 12-aminododecylphosphonic acid hydrochloride, (12-dodecylphosphonic acid)triethylammonium chloride, and (12-dodecylphosphonic acid)-N,N-dimethyl-N-octadecylammonium chloride.
[0037] Examples of compounds suitable for the compositions of the present invention that contain both phosphonate, hydrophobic, and imidazolium groups are 1-methyl-3-(dodecylphosphonic acid) imidazolium bromide and 1-methyl-3-(dodecylphosphonic acid) imidazolium bis(trifluoromethylsulfonyl)imide. An example of a compound with hydrophobic and triazolium groups is 1-methyl-1,2,4-(dodecylphosphonic acid) triazolium bromide.
[0038] Additionally, bioactive nanoparticles, such as silver nanoparticles, can be included in the functionalized composition.
[0039] An active organic compound can be a mixture of different molecules that have a specific effect.
[0040] In particular, phosphonic acids and hydrophobic or superhydrophobic group-containing compounds are preferred according to the invention, since they are compatible, soluble in ethanol and have very low reactivity with natural leather.
[0041] The compounds used in the present invention are commercially available or can be synthesized by methods known in the art from commercially available precursor compounds.
[0042] Tested Active Molecules (AM) Polyalkylene glycols (e.g., PAG, PEG) containing phosphonic acid (-PO3H2) groups, or C 16 H 30 N2PO3H2 (+) Br (-) (1-Methyl-3-(dodecylphosphonic acid)imidazolium)bromide;C 16 H 30 N2PO3H2 (+) C2F6NO4S2 (-) ;H3N (+) C 12 H 24 PO3H2Cl (-) Alkyl chains, fluoroalkyl chains, and / or linear polyether chains, such as (1-methyl-3-(dodecylphosphonic acid)imidazolium bis(trifluoromethylsulfonyl)imide)
[0043] Examples of test molecules can be seen in the table below.
[0044] The examples described herein show that the AM_7 solution (12,12,13,13,14,14,15,15,15-nonafluoropentadecylphosphonic acid) in ethanol has a concentration of 1.21·10 -2 mol L -1 This is called "Solution 1".
[0045] Sol-gel treated watch strap elements were externally tested for allergenic substances and none were found, and some of the treated bracelets were worn for six months without irritation. [Table 1]
[0046] process To functionalize the substrate according to the invention, various processes can be used, such as impregnation with organic solvents, the sol-gel process, or any other adapted method.
[0047] The organic solvent should be selected according to the nature of the substrate to be treated, the process temperature, and the solubility of the compounds.
[0048] A combination of processes is also possible.
[0049] Additionally, the substrate can be pretreated, such as by O2 or air plasma treatment, degassing, and / or cleaning.
[0050] With regard to impregnation, it was tested that structures containing natural leather were not damaged by ethanol at selected temperature and duration ranges.
[0051] To evaluate the samples and process steps, the water sorption of treated samples was measured.
[0052] First embodiment The impregnation method using active molecules and organic solvents includes the following steps: 1) selecting a substrate such as natural leather, vegetable leather, or textile; 2) Degassing the substrate to, among other things, remove excess water or control the amount of moisture in the object; 3) Treat the substrate with O2 plasma or air plasma for surface activation; 4) at least partially impregnating or coating the substrate with at least one selected active organic compound dissolved in a selected organic solvent; 5) Dry the treated substrate to remove any remaining liquid.
[0053] Base material The watch strap according to the invention may be a composite assembly of different types of leather and / or other materials, e.g. textiles. In this case, the watch strap has a multi-layer structure. The watch strap may include a liner, i.e. a layer that is in direct contact with the skin and is located on the inside of the watch strap.
[0054] Liners usually have two sides with different textures: the outer side is the side intended to be in contact with the skin, and the inner side is the side intended to be in contact with the ripstop layer or stuffing. The inner side is usually "rough", i.e., more porous.
[0055] The outermost surface layer is usually a leather layer, which determines the appearance of the watch strap when the watch is worn. There may also be a tear-resistant intermediate reinforcing layer (ripstop layer) and / or stuffing, etc. The stuffing may be of leather or another material. The various parts of the watch strap may be assembled by known techniques adapted to the material combination, i.e. sewing, gluing, etc.
[0056] All the different parts of a watch strap, i.e. liner, threads, stuffing, etc., can be separately functionalized according to the present invention and can be substrates.
[0057] Furthermore, only some or all of the components can be functionalized before the watch strap is assembled.
[0058] Alternatively, assembled watch straps or pre-assembled watch strap elements may be functionalized in accordance with the present invention.
[0059] All of these alternatives are suitable substrates according to the present invention.
[0060] Advantageously, the substrate is porous, for example natural leather, vegetable leather, i.e. natural leather substitutes consisting of fibres such as cellulose fibres extracted from the leaves of plants (Pinatex®, MycoTEX®, Tencel®, Lyocell®, pineapple, eucalyptus, bamboo, rubber tree, etc.), cork, cotton, hemp, silk, nylon, polyamide, aramid fabrics, etc.
[0061] To produce vegetable leather, long plant fibers, such as pineapple or eucalyptus fibers, plant materials such as mushroom mycelium, are used to create a nonwoven substrate that has an appearance very similar to natural leather.
[0062] Preferably, most of the components of the watch strap and its separate components, such as the liner, stuffing, and exterior layers, are made of porous materials, but some components, such as the tear protection layer (ripstop layer), are typically non-porous.
[0063] A porous substrate should be understood in a broad sense, being a matrix that includes interstitial spaces or voids through which, for example, air or solvent can pass. Porosity can take several forms, from interconnected microporosity, folds, and inclusions to macroporosity visible on the exterior surface. The spaces between textile threads or fibers can be assimilated into porosity.
[0064] Porous means in particular permeable to water vapor.
[0065] According to the present invention, natural leather is preferably used as the substrate.
[0066] Surface Treatment Before the functionalization treatment is applied, the surface of the substrate is prepared (pretreated) according to the method of the invention, the main steps of which are degassing and treatment with air or O2 plasma.
[0067] Degassing of substrates such as leather is important in the present invention to obtain good quality functionalization. It mainly ensures the removal of water in the liner. Degassing is usually carried out by heating to moderate temperatures under vacuum. One example of degassing consists in treating the substrate at 40°C for 16 hours under a pressure of 0.1 hPa.
[0068] Prior to applying the functionalization treatment of the present invention, the substrate may first be degassed and then "re-wetted" to a specific pre-selected humidity to stabilize the substrate and avoid further drying. Re-wetting can be done, for example, by storing the substrate in an environmental chamber at a specific pre-selected humidity and appropriate temperature until the system reaches equilibrium.
[0069] Treatment of substrates such as natural leather by irradiating the surface of the substrate with oxygen or air plasma at a selected power for a defined period of time has been shown to improve functionalization. Air plasma is preferred as it shows slightly better results than O2 plasma. The plasma is generated by conventional means known to those skilled in the art. The plasma treatment activates the surface of the substrate.
[0070] High power plasma does not improve surface activation. Results show that satisfactory results are obtained with a power of 25-60 W, and according to the invention, advantageously, a power of 30 W is used. Plasma may be applied, for example, using air or O2, at 25-60 W, 0.3-3 hPa, for 30 seconds to 6 minutes.
[0071] Longer treatment times do not improve surface activation, and treatment times of 30 seconds to 6 minutes give satisfactory results, advantageously periods of 30 seconds to 4 minutes, more advantageously periods of 30 seconds are employed.
[0072] 1.21·10 -2 mol L -1 After treatment with an ethanol solution of AM_7 at a concentration of 0.01, no significant effect of the plasma pressure fluctuation was observed. The results are shown in Table 2. [Table 2]
[0073] The results of this test are shown in Figure 1.
[0074] The highest functionalization is obtained with a preparatory treatment consisting of degassing at 40° C. under a pressure of 0.1 hPa for 16 h, followed by treatment with air plasma for 30 s at 30 W and 0.5 hPa.
[0075] Time after surface activation The functionalization should also be carried out immediately after the air or oxygen plasma pretreatment. It has been observed that the effect of the pretreatment disappears after only 30 minutes. Therefore, according to the method of the present invention, the functionalization treatment is carried out within 30 minutes after the plasma treatment has ended.
[0076] Functionalization For the functionalization treatment according to the invention, several parameters have been found to be important.
[0077] solvent The solvent is an organic solvent. Ethanol and isopropanol are suitable solvents for preparing the functionalized composition of the present invention.
[0078] Other aliphatic alcohols such as methanol, n-propanol, etc. are also suitable.
[0079] In addition, other organic solvents or combinations of organic solvents are possible, such as linear or cyclic alcohols, linear and cyclic ethers such as diethyl ether, diethyl tert butyl ether, tetrahydrofuran, dioxane, esters such as ethyl acetate, ketones such as acetone, diethyl ketone, ethyl methyl ketone, dipolar aprotic solvents, etc., as long as they protect the substrate and are compatible with the active molecule. The solvent should not have a strong odor and should not be highly toxic when in contact with the skin or when inhaled. In addition, it must be compatible with the substrate. The solvent is a polar solvent.
[0080] Surprisingly, ethanol shows the best results.
[0081] The most preferred organic solvent for use in the first embodiment of the present invention is ethanol.
[0082] process Typically, the functionalization is carried out by immersing the pretreated substrate in a solution of the active molecules, but other methods such as coating or spraying are also applicable. However, care must be taken to ensure that the solution is in intimate contact with the substrate so that the active molecules can fully penetrate the substrate.
[0083] The depth of penetration can be controlled by the viscosity of the composition or any other suitable method. The depth of penetration can be up to 100%.
[0084] Processing time After a certain immersion time, the water repellency of the treated surface is not further improved. For example, after 6 hours of impregnation, increasing the immersion time does not significantly affect the behavior of the substrate. Therefore, preferably, the immersion time is between 6 and 10 hours.
[0085] The immersion treatment can be carried out at room temperature, i.e., 22-25° C., at atmospheric pressure. Other conditions can also be adopted as long as they do not cause deterioration of the leather.
[0086] Concentration of active molecules The concentration of the active molecule should be as high as possible without forming a precipitate and should therefore be set as close as possible to the solubility limit of the active molecule in the respective solvent.
[0087] Optimal functionalization can be obtained by surface treatment with air plasma (e.g., 30 s, 30 W, 0.5 hPa) followed by immersion of the substrate in the active molecule-containing composition within 1 min after surface plasma treatment and immersing the substrate in the solution for 6 h for impregnation.
[0088] Drying The substrate is dried after impregnation. The desired drying temperature is 20°C to 85°C, preferably 25°C to 65°C, more preferably 30°C, in order to maintain the leather structure. Drying is carried out until the solvent has sufficiently evaporated. A period of 15 hours at 85°C can sufficiently evaporate the solvent. A period of 72 hours at 30°C can sufficiently evaporate the solvent.
[0089] Advantageously, the air is ventilated during drying.
[0090] For example, the substrate can be placed in a Greiner tube for drying.
[0091] Advantageously, the functionalized substrate is dried at 30° C. under ventilated air for 72 hours.
[0092] Optimal parameters for impregnation method Most preferably, the first embodiment comprises: ·Active molecules 12,12,13,13,14,14,15,15,15-Nonafluoropentadecylphosphonic acid (AM_7) ·solution 12,12,13,13,14,14,15,15,15-Nonafluoropentadecylphosphonic acid (AM_7) 1.21·10 in ethanol -2 mol L -1 Concentration of Optimized method Degas the substrate for 16 hours at 40°C under a pressure of 0.1 hPa; - Treat with air plasma at 30W, 30 seconds, 0.5hPa; · Proceed with impregnation within 1 minute after air plasma treatment; · Impregnating the substrate for 6 hours at room temperature, i.e. 22-25°C and atmospheric pressure; Dry the substrate (72 hours at 30°C in ventilated air).
[0093] Second embodiment In a second embodiment of the present invention, the leather substrate is impregnated with silica particles using a sol-gel process. Optionally and preferably, the sol-gel further comprises at least one active molecule. The active molecule can be selected from those described for the first embodiment of the present invention.
[0094] The method of the second embodiment of the present invention preferably comprises the following steps: 1) selecting a substrate; 2) Preparing a sol-gel solution under acidic or basic conditions: 3) aging the sol-gel; 4) at least partially impregnating or coating a substrate with the sol-gel; 5) drying the treated substrate to remove any remaining liquid; 6) Fixing the sol-gel on the substrate by tempering.
[0095] Base material In this embodiment, the same substrate as in the first embodiment can be suitably used.
[0096] Surface Treatment In this embodiment, no specific surface treatment is necessary, but alternatively, degassing and / or plasma pretreatment can be performed on the substrate to be treated, as described in the example of the first embodiment.
[0097] Sol-gel preparation The sol-gel solution can be prepared in acidic or basic conditions.
[0098] Generally, a basic sol-gel process (the so-called Strober process) forms silica (i.e., silicon dioxide) particles, preferably nanoparticles. A hydrolyzable precursor, typically tetraethoxysilane (TEOS), is first reacted with water in an alcohol solution, and then the resulting molecules are further reacted to form larger structures. This reaction produces silica particles with diameters of 50-2000 nm, depending on the conditions.
[0099] The acidic sol-gel silica method results in an extended network that can bond directly to the substrate surface and / or to the substrate's internal structure. The depth of penetration can be controlled by the viscosity of the sol-gel solution or any other suitable method. The depth of penetration can be up to 100%.
[0100] As precursors, hydrolyzable silanes such as tetraalkoxysilanes, alkyltrialkoxysilanes, dialkyldialkoxysilanes, etc., are suitable, where alkyl means linear, branched or cyclic alkyl having 1 to 8 carbon atoms, such as methyl, ethyl, propyl, butyl, pentyl, hexyl, cyclopentyl, cyclohexyl, etc., and alkoxy means alkoxy having 1 to 8 carbon atoms, such as methoxy, ethoxy, propoxy, butoxy, pentoxy, hexyloxy, etc., all of which may be linear or branched.
[0101] Preferably, tetraethoxysilane (TEOS), methyltrimethoxysilane (MTMOS), methoxypropyloxysilane, or butoxysilane are used according to the invention.
[0102] In the acidic procedure the pH is usually 0.5 to 4, preferably 1 to 2.5, most preferably 1.5 to 2. In the basic procedure the pH is usually 7 to 10, preferably 8 to 9.
[0103] Typically, the sol-gel is prepared from the precursor and a suitable solvent such as ethanol by stirring for a suitable time, e.g., 1-4 hours, preferably 2 hours, at elevated temperature of 30-85° C., preferably 40-70° C., typically 62° C., and then cooling to room temperature, i.e., 22-25° C. It is then coated on the leather substrate by a suitable method such as dipping, and the coated substrate is then tempered. For acidic conditions, the sol-gel solution preferably contains at least 3 g TEOS and 1.5-0.5 g HCl (0.5M) in 15-1 g EtOH (pH=1.5-2), optionally containing at least one active molecule at a concentration below or near its solubility limit in the sol-gel solution. For basic conditions, the conditions according to the Strober procedure using ammonia as catalyst are applied (see W Strober, A. Fink et EJ Bohn, J. Coll. Interface Sci, 1968, 26, 62). Optionally, the sol-gel contains at least the active molecule at a concentration below or near its solubility limit in the sol-gel solution.
[0104] Additionally, bioactive metal nanoparticles, preferably silver nanoparticles, can be added to the sol-gel.
[0105] Sol-gel solutions with or without active molecules The sol-gel is preferably prepared using the selected solution (suitable TEOS / EtOH ratio) by stirring and refluxing for a suitable time, e.g. 1-4 hours, preferably 2 hours, at a temperature of 30-85° C., preferably 40-70° C., typically 62° C. The sol-gel is allowed to cool for a suitable time, typically at least 20 minutes.
[0106] The sol-gel without active molecules was prepared by, for example, mixing 15.0 g of ethanol and 3.0 g of TEOS (3.2 mL, 1.44 10 -2 mol) and 1.1 g HCl (0.5 mol L -1 ) is obtained by mixing. The molar ratio TEOS:EtOH:H2O is selected according to need. Preferably, it is 1:23:4.
[0107] The leather substrate is treated, for example, by immersion in the sol-gel for about 5 minutes.
[0108] The substrate is then tempered in a high temperature oven for a specific time, usually 15 hours at 85°C.
[0109] Different batches of leather substrates may exhibit variations in treatment efficiency.
[0110] Concentration of active molecules in the sol-gel solution Preferably, active molecules (i.e. active organic compounds) can be added to the sol-gel prepared as described above. The active molecules are the same as those described in the first embodiment of the present invention. The preferred examples of active molecules are the same as those in the first embodiment. In particular, AM_7 and AM_5 have been tested in the sol-gel solution in this embodiment and are particularly preferred. One active molecule or a mixture of two or more different active molecules can be used. Usually, the active molecules are added to the sol-gel in the form of a solution in a suitable solvent, preferably ethanol.
[0111] The concentration ratio of the precursor of the sol-gel solution, such as TEOS, to the active molecule can be selected in a wide range from 10:1 to 100:1. Preferably, the TEOS:AM ratio is in the range of 15:1 to 65:1, and specifically 17:1, 43:1, and 62:1 may be used. However, variation in the concentration of the active molecule does not significantly affect the final performance of the treated leather.
[0112] Aging of sol-gel solutions by AM The term aging as used in this description does not necessarily correspond to a particular stage as is known in sol-gel chemistry: here it is used to describe an essentially laboratory operational step.
[0113] The term aging is used herein to designate stirring at a particular temperature for a particular time, typically under reflux. Despite changes in the reflux parameters used to age the sol-gels, there is no significant variation in water absorption between different samples.
[0114] Increasing the aging temperature maintains desirable sol-gel properties with the advantage of reducing processing time, however, the higher the reflux temperature the longer the cooling time.
[0115] The temperature range for aging the sol-gel solution can be 20° C. to 70° C. for 1 to 24 hours.
[0116] Advantageously, the cooling time can be limited while maintaining a reasonable duration of the ageing step, between 3 hours 50 minutes and 1 hour 45 minutes at a temperature between 56°C and 62°C.
[0117] Functionalization The sol-gel treatment of the substrate is carried out by dip coating or any other suitable technique known to those skilled in the art. A minimum treatment time (5-10 minutes) is selected to ensure complete impregnation of the sol-gel solution into the leather substrate.
[0118] Tempering of samples after functionalization with sol-gel solutions using AM After the sol-gel is coated on the substrate, it is tempered, i.e. heated to a certain temperature for a certain time. The tempering step achieves the polymerization of the sol-gel to silica and the evaporation of the solvent. If the tempering time is too short, the complete polymerization of the sol-gel and the total evaporation of the solvent cannot be achieved.
[0119] Increasing the temperature shortens the reaction time. However, higher temperatures may lead to deterioration of the leather. No visual changes were detected in the samples treated at 105°C and 120°C, but shrinkage of the leather samples was observed at temperatures above 85°C due to the nature of the substrate.
[0120] The tempering time must allow complete polymerization of the sol-gel and total evaporation of the solvent. The results show that the polymerization is complete after 17 hours at 65°C.
[0121] The minimum tempering time in the selected temperature range is approximately 5 hours. It is not necessary to temper for more than 24 hours. Samples were left overnight (approximately 15-17 hours) even if a shorter time would suffice.
[0122] In order to maintain the leather structure, the desired tempering temperature is preferably between 55°C and 85°C, preferably 65°C.
[0123] Sol-gel composition / ratio precursor / AM By changing the TEOS / AM ratio, the water absorption rate (%) of the leather substrate is affected.
[0124] In general, for each AM concentration there is an optimum range of precursor concentrations, above or below which the water absorption increases. The optimum ratio precursor (preferably TEOS) / active molecule can be selected by simple experimental tests.
[0125] An increase in AM concentration leads to an overall decrease in the water absorption rate of the leather substrate.
[0126] For example, as shown in Figure 5, a seven-fold increase in AM_7 concentration (1.21 10 -2 mol L -1 instead of 8.54 10 -2 mol L -1 ), only a 4% increase in water absorption is observed.
[0127] For example, when AM is 0.09 mol% relative to the total sol-gel solution containing AM, the TEOS concentration is preferably 2.9 mol%, and the water absorption is 17%. When AM_7 is the same 0.09 mol% and the TEOS concentration is 1.8 mol% or 3.8 mol%, the water absorption is higher.
[0128] "multilayer" Sequential processing can be used to improve the mechanical or physicochemical properties of the sol-gel process. That is, the steps of embodiment 2 are repeated using the same or different compositions. The layers, i.e., first layer without active molecules, then functional layer (i.e. layer with active molecules, etc.), can have the same or alternating properties. Or layers with different active molecules are also possible, such as no AM / AM / no AM, AM1 / AM2 / ..., AM1 / AM1, or any combination.
[0129] Mechanisms of Substrate Functionalization In the case of leather, the selected sol-gel solution has good chemical compatibility with the collagen structure. Thus, the three-dimensional network of the sol-gel is at least partially incorporated inside the leather. Analysis by SEM-EDX shows that the sol-gel prepared in acidic conditions penetrates inside the leather, preferably essentially through the entire thickness, without measurably affecting the topology of the leather. SEM-EDX could not identify a film or microstructure. However, silica was present in the observed zones. Considering the results, the sol-gel network appears to be a nanometric network directly bonded to the collagen network of the leather.
[0130] Analysis using SEM-EDX shows that the sol-gels prepared under basic conditions consist of silica particles with diameters between 50 and 2000 nm, which penetrate into the interior of the leather as a function of the porosity and size of the silica particles.
[0131] For SEM-EDX measurements, a MEB Zeiss Sigma 300 equipped with EDX was used.
[0132] The same logic applies to other porous substrates such as textiles. One effect of functionalization according to the second embodiment of the invention is to reduce or fill at least some of the pores in order to reduce the porosity in which microorganisms can find suitable growth conditions.
[0133] Optimal parameters for the sol-gel process Finally, the most preferred embodiment of the sol-gel embodiment of the present invention is the following: ·Active molecules 12,12,13,13,14,14,15,15,15-Nonafluoropentadecylphosphonic acid (AM_7) Sol-gel composition A tetraethoxysilane (TEOS) sol-gel solution with a molar ratio of TEOS:EtOH:H2O of 1:23:4 was prepared by dissolving 3.0 g of TEOS in 15.0 g of 1.21 10 -2The solution was prepared by mixing 12,12,13,13,14,14,15,15,15-nonafluoropentadecylphosphonic acid (AM_7) in ethanol at 1000 mol / L. The pH was adjusted to pH 2 by adding 1.5 g of HCl (0.5 M). Optimized method The mixture was refluxed at 62℃ for 2 hours with stirring to prepare a sol-gel. Allow the sol-gel to cool for at least 20 minutes. Treat the substrate by immersion and agitation for 5 minutes. ·Temper the substrate in an oven at 65°C for 17 hours. EXAMPLES
[0134] All of the examples described in this description are made with a natural leather liner made from Alzabel (calf leather).
[0135] The water absorption measurements in the examples were carried out using a desiccant scale that works on the principle of thermogravimetry. The experimental equipment was an OHAUS™ MB35. The samples to be measured are usually dried before the measurements (the last operation is a transfer in an oven or a preliminary measurement of the water uptake). The sample protocol is as follows: Place the weighing dish on the thermogravimeter. Completely immerse the sample in a container of ultrapure water for 1 minute. Wipe the sample off with a paper towel. Repeat the soaking and wiping process five times. Place the sample in the weighing pan of the thermogravimeter. Start the drying program. This program heats the sample to 60°C and tracks the weight of the sample as the water evaporates under the effect of the heat.
[0136] Comparison between active molecules We compare different active molecules on substrates treated with air plasma (30 or 60 W, 30 s, 0.5 hPa) and then with ethanol solution (concentration of active molecules 10 to 10 ) for 6 h at ambient temperature. -2 M).
[0137] The results of samples from tests 40, 41, 43, 44, and 45 indicate the presence of hydrophobic properties in these active molecules. These hydrophobically functionalized substrates exhibit no diffusion of water droplets through the surface of the substrate.
[0138] For the measurement, a drop of water is applied to the leather and the period of water absorption (visually observed) is recorded chronometerically.
[0139] Furthermore, in the case of substrates consisting of leather layer liners, either alone or in combination with a non-tearable layer and / or a filler and / or a finishing layer, water does not penetrate most liners after 48 hours of immersion in the functionalizing solution.
[0140] Surprisingly, surfaces functionalized with polyethylene glycol containing active molecules (tests 46-49) are relatively hydrophobic in terms of the drop angle, and not a single drop of water spreads through the treated surface. However, water uptake throughout the samples immersed in water is almost instantaneous and consistent with the use of active molecules. No differences are observed between PEG-containing active molecules with terminal OH functional groups and those with methoxy functional groups.
[0141] 56% is the maximum water increase when calf leather (Alzavel) is saturated with water. Different types of leather and different batches of the same leather type may have different water saturation levels, which is known to those skilled in the art.
[0142] The drop angle is measured by goniometry and the results are shown in Table 3. [Table 3]
[0143] Surface Treatment Degassing Degassing was performed by treating the substrate at 40° C. for 16 hours under a pressure of 0.1 hPa.
[0144] Comparing the water absorption rate with and without pre-degassing, the improvement in the case of pre-treatment (air or O2) with degassing is shown in Table 4 below. Samples 1 to 6 have an improvement of 1.21·10 -2 mol L -1 The nanoparticles were functionalized with an ethanol solution of AM_7 at a concentration of 0.01g / g. [Table 4]
[0145] Surface activation (see test results 4-21 in Table 5) Samples 4 to 21 are 1.21·10 -2 mol L -1 The nanoparticles were functionalized with an ethanol solution of AM_7 at a concentration of 0.01g / g.
[0146] The results in Table 5 below show that: Plasma vs. No Plasma Treatment of substrates such as natural leather by irradiating the surface of the substrate with oxygen or air plasma at a selected power for a defined period of time has been shown to improve functionalization. O2 vs. Air Plasma Air plasma shows slightly better results than O2 plasma. Plasma output The power of the plasma has been tested between 30 W and 300 W. Higher power plasma does not improve surface activation. Results show that satisfactory results are obtained with powers of 25 to 60 W, and advantageously a power of 30 W is used. Plasma treatment period Treatment times of 30 seconds to 8 minutes have been tested. Longer treatment times do not improve the activation of the surface. The results (see tests 17 to 21 in Table 5) show that treatment times of 30 seconds to 6 minutes give satisfactory results, advantageously durations of 30 seconds to 4 minutes, and more advantageously a duration of 30 seconds. Plasma pressure The pressure is varied between 0.1 hPa and 3 hPa. Note that no significant effect of pressure fluctuations on the plasma is observed, as shown in Figure 1.
[0147] As shown in Table 5 below, 1.21 10 -2 mol L -1 The optimal functionalization with a concentration of AM_7 was obtained with degassing and air plasma for 30 s, 30 W, and 0.5 hPa. [Table 5]
[0148] Sol-gel preparation Sol-gel The selected solution (matched TEOS / EtOH ratio) was used to prepare the sol-gel by stirring and refluxing at 62 °C for 2 h. The sol-gel was cooled for at least 20 min. 15.0 g of ethanol and 3.0 g of TEOS (3.2 mL, 1.44 10 -2 mol) and 1.1 g HCl (0.5 mol L -1 A sol-gel without active molecules was obtained by mixing TEOS, EtOH, and H2O in a molar ratio of 1:23:4.
[0149] Leather substrates were treated by immersion in the sol-gel for 5 minutes. The substrates were then tempered in an oven at 85°C for 15 hours. The results, summarized in Table 6, show that higher concentrations of TEOS in ethanol resulted in lower water absorption, up to a mass ratio of 1.11. The results are shown in Table 6. [Table 6]
[0150] It should be noted that different batches of leather substrates were used and there are variations in the efficiency of the treatment directly related to this.
[0151] Concentration of active molecules in the sol-gel solution Sol-gels were prepared using the selected solutions (matched molar concentrations) by stirring and refluxing for 2 hours at 62° C. The sol-gels were allowed to cool for at least 20 minutes.
[0152] Sol-gel A and sol-gel B are used.
[0153] Example 1: Sol-gel A A tetraethoxysilane (TEOS) sol-gel solution with a molar ratio of TEOS:EtOH:HO of 1:23:4 was prepared by dissolving 3.0 g of TEOS in 1.21 10 ethanol. -2 A 15.0 g solution of 12,12,13,13,14,14,15,15,15-nonafluoropentadecylphosphonic acid (AM_7) was mixed with 15.0 g of 12,12,13,13,14,14,15,15,15-nonafluoropentadecylphosphonic acid (AM_7) at 100 mol / L. The pH was adjusted by adding 1.5 g of HCl (0.5 M).
[0154] Example 2: Sol-gel B A tetraethoxysilane (TEOS) sol-gel solution with a molar ratio of TEOS:EtOH:HO of 1:23:4 was prepared by dissolving 3.0 g of TEOS in 1.21 10 -2 A solution of 15.0 g of mol / l n-octadecylphosphonic acid (AM_5) was prepared by mixing. The pH was adjusted by adding 1.5 g of HCl (0.5 M).
[0155] The leather substrate was treated by immersion in the sol-gel for 5 minutes. The substrate was then tempered in an oven at 85° C. for 15 hours. The results are shown in Table 7. [Table 7]
[0156] The use of n-octadecylphosphonic acid (AM_5) as the active molecule (sol-gel B) results in an interesting slightly lower performance than when 12,12,13,13,14,14,15,15,15-nonafluoropentadecylphosphonic acid (AM_7) is used (sol-gel A), but the difference is rather small.
[0157] In the range investigated, variations in the concentration of the active molecules do not significantly affect the final performance of the treated leather.
[0158] Example 3: Sol-gel C Tetraethoxysilane (TEOS) sol-gel solutions with a molar ratio of TEOS:EtOH:HO of 1:23:4 were prepared by mixing 3.0 g of TEOS with 15.0 g of ethanol and 0.66 wt% silver nanoparticles (40 nm or 60 nm). The pH was adjusted by adding 1.5 g of HCl (0.5 M).
[0159] Example 4: Sol-gel D A methyltrimethoxysilane (MTMOS) sol-gel solution with a molar ratio of 1:23:4 (MTMOS:EtOH:HO) was prepared by dissolving 3.0 g of MTMOS in 1.21 10 -2 A 15.0 g solution of 12,12,13,13,14,14,15,15,15-nonafluoropentadecylphosphonic acid (AM_7) was mixed with 15.0 g of 12,12,13,13,14,14,15,15,15-nonafluoropentadecylphosphonic acid (AM_7) at 100 mol / L. The pH was adjusted by adding 1.5 g of HCl (0.5 M).
[0160] Other Examples of Solutions 1.21·10 -2 mol L -1 A solution of n-octadecylphosphonic acid in ethanol was prepared at a given concentration of its solubility limit from 100 mL of 100 mL of 100% ethyl acetate. The solution was heated to approximately 60°C and stirred to completely dissolve the solid. Treatment of substrates with this second solution shows the same trends as solution 1.
[0161] Aging of sol-gel solutions and AM A significant decrease in water absorption was found between one untreated liner (54.6%) and the treated liners (27%–22%). However, there is no significant variation in water absorption between the different samples, despite the changes in the reflux parameters used for sol-gel aging.
[0162] The results of the corresponding tests are shown below in Table 8. As can be seen from the results in Table 8, the functionalization has a large effect on the inner surface of the liner, which is more porous than the outer surface. [Table 8]
[0163] A clear improvement in the hydrophobicity (drop angle) of the inner surface of the liner is measured between treated and untreated liners, but no variation is discernible between the different liners.
[0164] Functionalization The selected active molecule (AM) is mixed with a selected solvent. The mixing is carried out by mixing 10% of the selected active molecule in a selected solvent, such as ethanol. -4 The reaction is carried out for 6 hours in a solution of M~solubility limit. Other solvents or mixtures of solvents are also possible as long as they are compatible with the substrate and the sol-gel process. If necessary, the mixture can be heated and / or stirred until the active molecule is completely dissolved.
[0165] solvent Ethanol and isopropanol have been tested and both are suitable.
[0166] Time after surface activation (Tests 23, 33-35) Functionalization should also be performed immediately after pretreatment with oxygen or air plasma. It was observed that the effect of plasma pretreatment essentially disappeared after only 30 minutes. The results are shown in Table 9. [Table 9]
[0167] The results of this test are shown in Figure 2.
[0168] Processing time (tests 22-25) It has been shown that after a certain immersion time, the water repellency of the treated surface does not improve. -2 mol L -1 For AM_7 at the concentration of (solution 1), after 6 hours of impregnation the absorption is 18%, increasing the time does not have a significant effect on the behavior of the substrate. The results are shown in Table 10. [Table 10]
[0169] The results of this test are shown in FIG.
[0170] Solution Concentration (Tests 23 and 26-29) The concentration of the active molecule should be as high as possible without forming a precipitate and should therefore be set as close as possible to the solubility limit of the active molecule in the respective solvent, as shown in Table 11.
[0171] 1.21·10 in ethanol -2 mol L -1 Optimal functionalization with a concentration of AM_7 (solution 1) was obtained with air plasma (30 s, 30 W, 0.5 hPa) followed by immersion of the substrate for less than 1 min after surface plasma treatment and leaving the substrate immersed in the solution for 6 h. [Table 11]
[0172] The results of this test are shown in FIG.
[0173] Tempering of samples after functionalization with sol-gel solutions and AM Sol-gel A containing AM_7 as above was prepared by stirring at reflux for 3.5 hours at 56°C (aging of the sol-gel solution). The sol-gel was allowed to cool for at least 20 minutes. Leather substrates were treated by immersion in the sol-gel for 5 minutes under the above conditions.
[0174] The substrates were then tempered in an oven for various times and temperatures, with the results shown in Table 12. [Table 12]
[0175] Tests 62 and 68 have a high first water absorption reading and a low second reading. This observation may be related to the tempering time, which seems too short to allow complete polymerization of the sol-gel and complete evaporation of the solvent.
[0176] Increasing the temperature shortens the reaction time. However, higher temperatures may lead to deterioration of the leather. No visual changes were detected in the samples treated at 105°C and 120°C, but shrinkage of the leather samples was observed at temperatures above 85°C due to the nature of the substrate.
[0177] Drying The substrate is dried after impregnation. The desired drying temperature is 20°C to 85°C, preferably 25°C to 65°C, more preferably 30°C, to maintain the leather structure. Dry until the solvent has evaporated. A period of 15 hours at 85°C allows sufficient evaporation of the solvent. A period of 72 hours at 30°C allows sufficient evaporation of the solvent. Advantageously, air is ventilated during drying.
[0178] For example, the substrate can be placed in a Greiner tube for drying.
[0179] Advantageously, the substrate is dried at 30° C. under ventilated air for 72 hours.
[0180] Sol-gel composition The water absorption rates obtained with different TEOS / AM_7 ratios are shown in Figure 5.
[0181] Figure 5 shows that changing the TEOS / AM_7 ratio affects the water absorption (%) of the leather substrate. For each concentration of AM_7, there is an optimal range of TEOS concentration, above or below this range the water absorption increases.
[0182] For example, when AM is 0.09 mol% relative to the total sol-gel solution containing AM, the TEOS concentration is preferably 2.9 mol%, and the water absorption is 17%. When the same 0.09 mol% AM_7 and TEOS concentrations are 1.8 mol% or 3.8 mol%, the water absorption is higher.
[0183] Increasing AM_7 concentration leads to an overall decrease in water absorption of the leather substrate.
[0184] A seven-fold increase in AM_7 concentration (1.21 10 -2 mol L -1 Instead of 8.54 10 -2 mol L -1 ), as shown in Figure 5, an increase in water absorption of only 4% is observed.
Claims
1. A composition for impregnating a watch strap or part thereof, said composition comprising: a) an organic solvent selected from ethanol or isopropanol, or a sol-gel comprising silica particles; b) i.CH 3 (CH 2 ) n P.O. 3 H 2 where n is 2 to 18, and ii. CF 3 (CF 2 ) n (CH 2 ) m P.O. 3 H 2 wherein n and m are 2 to 18, and m and n are the same or different; At least one active organic compound selected from and the active organic compound optionally comprises i. Formula: -O((CH 2 ) m O) n - a polyalkylene glycol group, where m is 2, 3 or 4, n is 2 to 18, and has a hydrogen or an alkyl having 1 to 6 carbon atoms as a terminal group; ii. An imidazolium group, a triazolium group, or an ammonium group which may be substituted with 1 to 3 alkyl groups having 1 to 6 carbon atoms, or with 1 or 2 alkyl groups having 1 to 6 carbon atoms and an alkyl group having 10 to 18 carbon atoms. At least one functional group selected from The composition, wherein the watch strap or part thereof is selected from natural leather, natural leather substitutes made from vegetable fibers, cork, and textiles, and combinations thereof.
2. The composition of claim 1 further comprising silver nanoparticles.
3. The composition according to claim 1 or 2, wherein the organic solvent is ethanol.
4. Formula: -O((CH 2 ) m O) n The composition according to claim 1, wherein m is 2.
5. 1. A method for functionalizing a substrate by impregnation, comprising the steps of: i. selecting a substrate; ii. Degassing the substrate; iii. treating the substrate with oxygen plasma or air plasma; iv. at least partially impregnating the substrate with the composition according to any one of claims 1 to 4, the composition comprising an organic solvent selected from ethanol or isopropanol; v. drying the treated substrate; Including, the substrate is a watch strap or part thereof; and The method, wherein the substrate is selected from natural leather, natural leather substitutes made from plant fibers, cork, and textiles, and combinations thereof.
6. Use of a composition according to any one of claims 1 to 4 for reducing the water absorption rate of a substrate or one or more parts thereof, said substrate being a watch strap, The substrate or one or more parts thereof is selected from natural leather, natural leather substitutes made from plant fibers, cork, and textiles, and combinations thereof; and The above use, wherein the composition is used to impregnate the substrate or one or more parts thereof.
7. A watch strap obtainable by the method according to claim 5.
Citation Information
Patent Citations
Silica-fixed fiber material and production thereof
JP1992202848A
Fiber product treating agent and method for treating fiber product
JP2002069842A
How to prevent contamination on the surface of aluminum products
JP2002518594A
Lotioned wipes to reduce adhesion of dirt or exudates to skin
JP2009539465A
Method for adsorbing antibacterial / deodorant composition on fiber material
JP2013108203A